Application of COBIT 5 for Hospital Services Management Information System Audit - Ida Bagus Leo Mahadya Suta; I Gusti Ngurah Agung Surya Mahendra; Made Sudarma (International Journal of Engineering and Emerging Technology, 2018)
We conduct research on hospital management information system management audits where management includes services to patient queuing times and medical personnel who implement COBIT 5 with the Deliver, Service, Support (DSS) domain from the results of the application of DSS domains on COBIT 5 then maturity levels are obtained an average of 2.2 to 2.8 who have an IT governance process in hospital services has a pattern that is repeatedly performed